2011
DOI: 10.4103/2230-8210.83402
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher′s disease

Abstract: Gaucher's disease (GD) is the most common amongst the various disorders classified under the lysosomal storage disorders. GD is a model for applications of molecular medicine to clinical delineation, diagnosis, and treatment. The multiorgan and varied presentation of the disease makes it a challenge to diagnose GD early. The advent of enzyme replacement therapy in the early 1990s changed the management, and survival, of patients with GD. In addition to this, development of substrate reduction, pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
6
0
6
Order By: Relevance
“…types II and III that is followed by involvement of nervous system. Several studies have reported [7]. Deposition of Gaucher cells results in fibrosis and pressure on vessels, and finally will cause dilation and increasing pressure on the portal vein in a patient [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…types II and III that is followed by involvement of nervous system. Several studies have reported [7]. Deposition of Gaucher cells results in fibrosis and pressure on vessels, and finally will cause dilation and increasing pressure on the portal vein in a patient [8].…”
Section: Discussionmentioning
confidence: 99%
“…Gaucher disease is usually associated with demonstration of pseudo-Gaucher cells in bone marrow [1]. The activity of Glucocerebrosidase enzyme is the best criteria for detecting GD in all its types [7]. Several authors emphasize this point that there is no relationship between the remaining activity of acid beta-glucosidase enzyme and clinical intensity and severity or type of GD [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with debilitating visceral, haematological and skeletal manifestations characterized by liver and/or spleen enlargement, anaemia, fatigue, thrombocytopenia leading to easy bruising and bleeding episodes, and debilitating bone pain and bone fractures [ 5 ]. The two more severe forms of Gaucher disease, type 2 which manifests in early infancy and type 3 which manifests in early childhood, are associated in addition with overt neurological symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Es la enfermedad más frecuente del grupo de las enfermedades de depósito lisosomal comprendidas dentro de los errores innatos del metabolismo (1). La enfermedad de Gaucher se debe a mutaciones en el gen responsable de la síntesis de la enzima lisosomal b-glucocerebrosidasa ácida, también llamada ß-Glucosidasa ácida, (o ß-GA), cuyos locus se ubica en 1q21, es decir en la banda uno de la región 2 del brazo largo del cromosoma 1.…”
Section: Introductionunclassified